Intake of Nutritional Supplements among People Exercising in Gyms in Beirut City - D. El Khoury; S. Antoine-Jonville (Journal of Nutrition and Metabolism)
The use of nutritional supplements among exercisers in gyms has been never investigated in the Middle East. The aim of the current study was to assess the prevalence intake of nutritional supplements and the potential influencing factors among people exercising in gyms in Beirut city. In this cross-sectional study, 512 exercisers, aged between 20 and 50 years, were randomly selected from gyms. The intake of nutritional supplements was reported among 36.3% (95% confidence interval 32.2–40.5) of participants, with a weak presence of medical supervision. Patterns of supplement use differed by gender and age. Men and younger exercisers were found to focus on supplements associated with performance enhancement and muscle building, while women and older exercisers were more concerned with health-promoting products such as vitamins, minerals, and herbal supplements. An appropriate dissemination of accurate and scientifically sound information regarding the benefits and side effects of nutritional supplements is highly recommended in the sports environment in Beirut city.